A proposed neural control for the trajectory tracking of a nonholonomic mobile robot with disturbances - Martins, Nardênio A.; De Alencar, Maycol; Lombardi, Warody C.; Bertol, Douglas W.; De Pieri, Edson R.; Filho, Humberto F. [UNESP] (Springer Nature, 2012)
In this paper, a trajectory tracking control problem for a nonholonomic mobile robot by the integration of a kinematic neural controller (KNC) and a torque neural controller (TNC) is proposed, where both the kinematic and dynamic models contains disturbances. The KNC is a variable structure controller (VSC) based on the sliding mode control theory (SMC), and applied to compensate the kinematic disturbances. The TNC is a inertia-based controller constituted of a dynamic neural controller (DNC) and a robust neural compensator (RNC), and applied to compensate the mobile robot dynamics, and bounded unknown disturbances. Stability analysis with basis on Lyapunov method and simulations results are provided to show the effectiveness of the proposed approach. © 2012 Springer-Verlag.
Keywords: Lyapunov theory; neural networks; Nonholonomic mobile robot; sliding mode control theory; trajectory tracking; variable structure control; Bounded unknown disturbances; Dynamic neural controllers; Lyapunov theories; Mobile robot dynamics; Neural control; Neural controller; Non-holonomic mobile robots; Stability analysis; Trajectory tracking; Trajectory tracking control; Variable structure controller; Kinematics; Lyapunov methods; Neural networks; Sliding mode control; Variable structure control; Mobile robots